Medical ethics education as translational bioethics - Young, Peter D.; Papanikitas, Andrew N.; Spicer, John (2024)
We suggest that in the particular context of medical education, ethics can be considered in a similar way to other kinds of knowledge that are categorised and shaped by academics in the context of wider society. Moreover, the study of medical ethics education is translational in a manner loosely analogous to the study of medical education as adjunct to translational medicine. Some have suggested there is merit in the idea that much as translational research attempts to connect the laboratory scientist's work to its implications for patient care, translational ethics focuses on bringing ethics scholarship into the sphere of personal and public action. We distinguish the term ‘translational ethics’ (the study of ethics being translated between academy, classroom and clinic) from other prominent definitions in the bioethics literature. To do this, we build off a notion of knowledge translation that focuses on the nonlinear movement of information that comes to professionals through multiple competing sources. We suggest that this knowledge, and particularly knowledge about ethics, becomes embodied by the individual. It is through a reflective practice that internally embedded ethics knowledge might be modified, and this work might be best carried out with a moral community that maintains a sense of practical wisdom. Applying this translational approach to the study of medical ethics education can be both academically relevant and practically useful. This view of translation can help bridge the evident, multidirectional relationships between research, education and performance. It might also create further opportunities to develop medical ethics education theory.
Keywords: Medical Ethics; knowledge translation; education theory